Analysis of the Control Effect and Parameter Optimisation of Urban Surface Deformation in Underground Coal Mining with Solid Backfilling - Jiaqi Wang; Jixiong Zhang; Qiang Zhang; Zhongya Wu; Qi Zhang; Yunbo Wang; Difa Gao (Advances in Civil Engineering)
To solve the problems of surface deformation and destruction of buildings caused by urban mining and realise the coordinated development of mining cities, the solid backfilling method was used to extract coal resources beneath the buildings of Tangshan. Based on surface deformation monitoring data of the continuously operating reference station (CORS) system for the past 5 years, the surface deformation process caused by solid backfilling was analysed. The final results revealed a maximum surface subsidence of 66 mm in the T zone coal area and 31 mm in the F zone area. Furthermore, the surface control effects of the caving method and the solid backfilling method were compared and analysed, and it was shown that solid backfilling could meet the surface building setup requirements. Moreover, based on the probability integral method, the effects on surface deformation due to the surface length of the F zone, compression ratio, and coal pillar width were analysed, and the effects on the prediction results due to the subsidence factor, tangent of the major effective angle, and offset distance of the inflection point were studied. The results showed that the compression ratio is the main factor controlling the surface deformation and that it should be kept above 80% for solid backfilling of urban mines. The subsidence factor should be 0.82, and the tangent of the major effective angle should be 2.15 when the surface subsidence of solid backfilling is to be predicted. This paper provides a technical reference for the realisation of urban mining with solid backfilling.